2012
DOI: 10.1017/s1755267212000644
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Lucinoma heroica (Mollusca: Bivalvia: Lucinidae) in the minimum oxygen zone in the Gulf of California, Mexico

Abstract: From samples taken during the oceanographic cruises TALUD IV-X in the southern and central Gulf of California, Mexico, 291 specimens of Lucinoma heroica were obtained in a depth interval of 731 to 991 m. The species occurred under conditions of severe (,0.1 ml l 21 O 2 ) and moderate hypoxia (0.1 -0.5 ml l 21 O 2 ). The correlation between height and length of the shell showed isometric growth with a trimodal size distribution, showing an average interval of 3.75 mm to 47.40 mm in height and 4.96 mm to 54.00 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In our study we found that depth and temperature were also important environmental factors related to variation in the composition of benthic megafauna as reported in other studies of the southern and central regions in the GoC (Hendrickx, 1996(Hendrickx, , 2006Méndez, 2007;Zamorano et al, 2007;Zamorano and Hendrickx, 2012). However, multiple interacting factors ranging from hydrographic (DO, water masses) to food supply and interactions act in synergy with DO and substratum type to influence the structure of these communities.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In our study we found that depth and temperature were also important environmental factors related to variation in the composition of benthic megafauna as reported in other studies of the southern and central regions in the GoC (Hendrickx, 1996(Hendrickx, , 2006Méndez, 2007;Zamorano et al, 2007;Zamorano and Hendrickx, 2012). However, multiple interacting factors ranging from hydrographic (DO, water masses) to food supply and interactions act in synergy with DO and substratum type to influence the structure of these communities.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, low taxonomic richness of megabenthic fauna was observed at depths with reduced DO and greater cover of soft sediment in the LB of the OMZ. Several studies in this region (Méndez, 2007;Zamorano et al, 2007;Zamorano and Hendrickx, 2012;Hendrickx and Serrano, 2014;Hinojosa-Corona, 2014;Hendrickx et al, 2016;Papiol and Hendrickx, 2016) have reported that the OMZ is coupled closely to the diversity, composition, abundance and distribution of megafauna inhabiting the water column and the benthos. Differences in the tolerances of megafauna to OMZ conditions very likely influence the shift in the species composition of communities in the LTZ (Levin, 2003;Gooday et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some species of mollusks (e.g., Lucinoma spp.) are known to tolerate extremely low oxygen concentrations and are able to survive in severe hypoxic conditions ( Zamorano and Hendrickx 2012 ; Vaquer-Sunyer and Duarte 2008 ). Except for two samples (i.e., Jupiteria pontonia and Limatula cf.…”
Section: Discussionmentioning
confidence: 99%